Veronica arguteserrata Reg. et Schmalh. – a New Alien Species for Ukrainian Flora (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The Asian species Veronica arguteserrata that had been slowly penetrating to Europe is first found in Odessa (Ukraine).
Keywords: Veronica arguteserrata , flora, Ukraine, alien species.